PEMANFAATAN PENGINDERAAN JAUH DAN SIG UNTUK PEMETAAN KERAWANAN PANGAN BERDASARKAN PENDEKATAN AGROEKOSISTEM DI KABUPATEN BANJARNEGARA - , DIAN RIMBAYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Food vulnerability is one of the significant disaster that needs to be studied because food is a basic need for human life. One of the Regency in Central Java province that is affected by food vulnerability is Banjarnegara Regency. Factors that could cause food vulnerability are the change of agricultural land into non - agricultural and population increase. This research aims to utilize Landsat TM 5 image remote sensing for the identification and mapping of the physical parameters of land in developing Agroecosystems Zone, as well as to determine the distribution of food vulnerability in Banjarnegara Regency. The method used is Remote Sensing and GIS with agroecosystem approach. Five parameters that support Agroecosystem approach are landforms, elevation, slope, rainfall and soil type. The fifth parameter has been overley in order to obtain 79 land units. Each land unit conducted field tests and interviews related to productivity and type of staple food, in order to obtain 17 zones agroecosystems based on common characteristics of the land, the productivity of staple food and staple plant species. Staple crops in the district include the Banjarnegara rice, maize, cassava, sweet potato and potato. The 17 zone agroecosystems and their characteristics can be determined each district that is prone to food by calculating calorie needs and the availability of calories each district, so that the obtained results adequacy of calories each district. Average yield of productivity are 5,64 tons / ha for rice, 7.6 tons / ha for maize, 16.825 tons / ha for potato, 22 tons / ha for cassava and 18 tons / ha for sweet potato. These calculations derive the result that from 20 districts in Banjarnegara there is only one district that experienced food vulnerability, the District Banjarnegara.